Mediterranean Sea Literacy: When Ocean Literacy becomes region-specific - MOKOS, MELITA; CHEIMONOPOULOU, MARIA TH.; KOULOURI, PANAYOTA; PREVIATI, MONICA; REALDON, GIULIA; SANTORO, FRANCESCA; MOGIAS, ATHANASIOS; BOUBONARI, THEODORA; GAZO, MANEL; SATTA, ALESSIO; IOAKEIMIDIS, CHRISTOS; TOJEIRO, ALBA; et al. (Mediterranean Marine Science, 2020)
Ocean Literacy (OL) has been defined as an understanding of the ocean’s influence on people and their influence on the ocean. The OL movement was born in the US and its framework consisted of seven essential principles and 45 fundamental concepts; it is now largely accepted worldwide for use in both formal (schools and universities) and non-formal (research institutes, aquaria, museums, etc.) education settings. Based on this framework, marine scientists and educators developed the “Mediterranean Sea Literacy” (MSL) guide adapted to the specificities of the Mediterranean region, presented here. The MSL principles (7) and concepts (43), serving as guidance for research, education, informed decision-making, and improved citizens’ lifestyles, aim to contribute to environmental protection, conservation, and restoration of the Mediterranean Sea as well as to help to achieve a blue innovative and sustainable economy.